Enhanced Authentication for Commercial Video Services - HUANG, Xinyi (Institutional Knowledge at Singapore Management University, 2012)
The advance in information technology has made video service a market with great commercial value. As an example, in-vehicle infotainment has been introduced to vehicles with which customers can enjoy subscribed media services wherever they are. This paper investigates the authentication in commercial video services using a recently proposed protocol, the Sun–Leu protocol, as baseline. Several important security and performance requirements are revisited, including mutual authentication, anonymous authentication, one-to-many delivery, low communication cost and the security against replay attacks. We provide a detailed analysis of the Sun–Leu protocol against these requirements, based on which an enhanced authentication scheme is proposed. The new scheme is designed within the framework of the Sun–Leu protocol, preserves all merits of the original protocol and provides a higher level of security for video communication services.